ERK is involved in the regulation of CpG ODN 2395 on the expression levels of anti-lipopolysaccharide factors in Chinese mitten crab, Eriocheir sinensis. Issue 131 (December 2022) - Huang, Shu; Ma, Yuhan; Wang, Fengchi; Li, Jiaming; Yang, Zhichao; Jiang, Yusheng; Chen, Xi; Hu, Shengyang; Yi, Qilin
Abstract: CpG oligodeoxynucleotides (ODN), as an effective adjuvant or immunopotentiator, activate the immune system and induce various immune responses. Recently, it has also been reported that high dose of CpG ODN can lead to immunosuppression. However, the underlying mechanism of CpG ODN-mediated immune response remains largely unknown in invertebrates. In the present study, the role of ERK in regulating expression levels of anti-lipopolysaccharide factors (ALFs) induced by different doses of CpG ODN 2395 was analyzed in Chinese mitten crab, Eriocheir sinensis . The mRNA expression levels of Es ALFs ( Es ALF1, Es ALF2 and Es ALF3) and Es ERK in haemocytes were observed to increase from 6 h to 48 h post low doses of CpG ODN 2395 (0.5 μg and 2.5 μg) stimulation, while they were suppressed after high dose of CpG ODN 2395 (12.5 μg) injection. Meanwhile, the phosphorylation levels of ERK in haemocytes were significantly promoted after low doses of CpG ODN 2395 injection, and a reduce level of ERK phosphorylation was observed after high dose of CpG ODN 2395 injection. Further investigation showed that the expression levels of Es ALFs induced by CpG ODN 2395 were markedly down-regulated after knocking down the expression of Es ERK. Similarly, the Es ALFs mRNA expression were also inhibited post different doses of CpG ODN 2395 stimulation in PD98059 (ERK inhibitor) injection crabs. These results collectively suggest that ERK is involved in regulating the expression level of Es ALFs induced by different dose of CpG ODN 2395 in Chinese mitten crab, which contribute to the understanding of the regulation of CpG ODN involving in immune response in crustaceans. Highlights: Low dose of CpG ODN 2395 markedly enhanced Es ALFs and Es ERK expression. High dose of CpG ODN 2395 significantly reduced Es ALFs and Es ERK expression. Es ERK acts as a regulator involving in the Es ALFs expression induced by CpG ODN 2395.